The Use of Constructivist Approach in Learning Short Stories Writing of Nineth Grade Students of SMP Negeri 2 Nambioman Bapai - Rahmah, St.; Yani, Juli (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
Writing skills, better known as composing, are one of the four language skills taught to students who learn languages, one of which is writing short stories. As a productive skill, writing requires students to be able to explore, discover, and express ideas, feelings, experiences, and the appropriate use of language. However, in reality, not all students can show these abilities. This research focuses on the influence of learning to write short stories through a constructivism approach. The purpose of this study is to find out whether the constructivism approach used can help and make it easier for students to improve their short story writing skills before and after using the constructivism approach in writing short stories. In this study, the author uses a quasi-experimental method, without a control class or a comparison class. In the use of all these experiments, the author uses the research design of the initial test, treatment, and final test. Learning to write short stories in the initial test got an average of 69.71 and in the final test got an average of 77.59. In the results oft calculating>t table is obtained 10.001 > 2.028, as well as a significance of 0.00 < 0.05. This proves that the constructivism method is effective and very reliable applied to learning to write short stories. The learning results using the constructivism approach are proven to help students find ideas and thoughts in writing short stories by paying attention to the elements that build short stories (theme, plot, setting) and language (spelling and diction).